The Effect of Regular and Unregular Exercise against Network Damage - Jafaruddin Jafaruddin; Indah Lestari; Sumarjo Sumarjo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to determine the difference in the effect of regular and irregular exercise on tissue damage, while the indicator used to determine tissue damage was creatine kinase. This study is an experimental laboratory study with a randomized control group post-test-only design, using a sample of 39 male Rattus norvegicus strain wistar mice divided into 3 groups consisting of: swimming exercise group regularly with exercise frequency 3 times per week, swimming training group irregularly. With irregular exercise frequency and control group who were not given swimming training. The treatment was carried out for 3 months. From the results of the study, the following results were obtained: there was a very significant difference (p < 0. 01) between the groups of regular and irregular exercise on tissue damage, where irregular exercise has a greater effect on tissue damage. Based on the results of the study, it can be concluded that irregular exercise has a greater potential for tissue damage than regular exercise.